PERTIMBANGAN HAKIM MENJATUHKAN VRIJSPRAAK DALAM TINDAK PIDANA NARKOTIKA (PUTUSAN NOMOR 1434/PIDSUS/2018/PN MKS) - Abiyyu Ahmad Patria; Kristiyadi Kristiyadi (Sebelas Maret University, 2023)
The author conducted research related to the evidentiary process at the trial that gave an acquittal against narcotics crime, whether the Panel of Judges in giving an acquittal was by following existing regulations in Indonesia, especially in the Criminal Procedure Code (KUHAP) and in Act of the Republic of Indonesia Number 35 Year 2009 Concerning Narcotics. This research is normative law research. In this legal research, the author uses primary legal materials, secondary legal materials, and tertiary legal materials obtained through literature study by the topic of the case that the author takes. This legal writing uses a qualitative analysis technique with a deductive syllogism method. Based on the results of the study, Verdict Number: 1434/Pid.Sus/2018/PN.Mks is in accordance with Article 183 jo Article 191 of the Criminal Procedure Code (KUHAP), this is in accordance with the considerations given by the Judge in the evidentiary process in the trial. This research aims to provide input to law enforcers to be careful in handling cases so that it does not occur in the verdict of acquittal of narcotics crime cases by following per under the objectives of in Act of the Republic of Indonesia Number 35 Year 2009 Concerning Narcotics.Keywords: Acquittal; Evidence; Narcotics.